Variation in seed yield and nutrient contents in African yam bean (sphenostylis stenocarpa) (2008)
Nine African yam bean accessions were evaluated for seed yield and other reproductive characters Significant differences were observed for seed yield, 100 seed weight and number of days to 50% flowering. Seed yield among the accessions ranged from 24.79 to 118.33 g per plant. Average number of seeds per pod was from 13.33 to 19.33, 100 seed weight varied between 19.69 to 28.22 g, while pod length also differed from 19.57 to 28.00 cm. The protein content of the African yam bean accessions were comparable to that of cowpea, but the concentrations of the anti-nutritional factors were significantly higher in the African yam bean accessions. Although the African yam bean accessions with low anti-nutritional factors were low yielding, they can be recombined with the high yielding accessions in developing improved varieties.